STRUKTUR DAN MAKNA MANTRA DALAM UPACARA ADAT BASAYAK DAYAK BAKATI DI DESA LESABELA KECAMATAN LEDO - Yesi, Yesi; Syam, Christanto; Seli, Sesilia (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
Spells are considered to have magical powers, the wording has rhyme and the delivery has intonation which is often called rhythm. Research problem how to rhyme the Basayak spells, how to concrete words in the spells, what the meaning of the Basayak spells is, and how to implement research results in Indonesian language learning in schools. This research uses descriptive methods, a form of qualitative research, and uses a structural approach. The source of research data is the Basayak spells spoken by a shaman. The research data is the structure and meaning of mantras obtained from spells texts. The results of research data analysis on the Basayak spells include: (1) rhyme which includes; (a) rhyme according to the correspondence of sounds in words or syllables consisting of full, absolute, half, stem, assonance, consonance, dissonance, sequence, and visual rhyme; (b) rhyme according to the position of the words in the sentence line consisting of initial, middle and final rhymes; (c) rhyme based on the position of its partner in the stanza consisting of continuous, hug, cross, twin, break and free rhyme (2) concrete words include concrete words that describe the senses of sight, hearing, touch and taste; (3) meanings which include religious meaning, personality, meaning related to nature, and society (4) The Basayak spelss can be implemented in learning at school by implementing the Independent Learning Curriculum.